Spillover Effects and R&D-Cooperations - The Influence of Market Structure - Anita Wölfl (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2000)
This paper examines empirically the role of market structure for the influence of spill-over effects on R&D-cooperations. The results of a microeconometric analysis, based on firm data on innovation, let in general presume that with intensified competition also the influence of spillovers on R&D-cooperation increases. However, competition seems to induce firms to search for effective firm-specific appropriation facilities first. Spillovers that are sufficiently high such that the internalisation effect from R&D-cooperation more than outweighs the competitive effect from research, only arise whenever firms are not able to protect their research results through any appropriation facility. Additionally, there is some evidence that spillover effects may even hinder firms from cooperating in R&D when there is intensive competition on the research stage.
urn:nbn:de:gbv:3:2-18528
Keywords: O31; O32; O34; L13; L14; 330; spillover effects; R&D-cooperation; competition; market structure; microeconometric analysis; Forschungskooperation; Industrielle Forschung; Spillover-Effekt; Ökonomischer Anreiz; Internalisierung externer Effekte; Marktstruktur; Wettbewerb; Schätzung; Deutschland